Perioperative nursing of a newborn with Beckwith-Wiedemann syndrome - Zhu Qian; Wang Yue; Hou Jie-Yi; Wang Si-Yu (Sciendo, 2022)
Objective: To explore the perioperative nursing of a newborn with Beckwith-Wiedemann syndrome.